Contactless Remote Monitoring for the Detection of Drug Effects in People Living With Dementia: A Case Study on the Use of Mirtazapine to Treat Insomnia - Ana Mirza-Davies; Eyal Soreq; David Sharp (BJPsych Open)
Aims: Safe and effective prescribing in people living with dementia (PLWD) is particularly challenging due to the increased risk of adverse events, polypharmacy and potentially inappropriate medications. Cognitive impairment and reliance on caregivers to report symptoms can further complicate the assessment of drug benefits. This case study demonstrates how novel contactless monitoring could address these challenges by enabling remote evaluation of drug effects in PLWD.